2011
DOI: 10.1038/nsmb.2186
|View full text |Cite|
|
Sign up to set email alerts
|

Tudor domain ERI-5 tethers an RNA-dependent RNA polymerase to DCR-1 to potentiate endo-RNAi

Abstract: Endogenous RNA interference (endo-RNAi) pathways employ a variety of mechanisms to generate short-interfering (si) RNAs and to mediate gene silencing. In Caenorhabditis elegans, DCR-1 is essential for competing RNAi pathways - the ERI endo-RNAi pathway and the exogenous RNAi pathway. Here, we demonstrate that DCR-1 forms exclusive complexes in each pathway and further define the ERI–DCR-1 complex (ERIC). We show that the tandem-tudor protein ERI-5 potentiates ERI endo-RNAi by tethering an RNA-dependent RNA pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
74
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(87 citation statements)
references
References 40 publications
6
74
2
Order By: Relevance
“…ERI-9 was previously shown to be required for 26G-RNA biogenesis (Pavelec et al, 2009). Consistent with the association of RDE-8 with ERI/Dicer complex components (Duchaine et al, 2006), we found that RDE-8 also co-IPs with the SAP-domain exonuclease ERI-1b (Figure S3; Kennedy et al, 2004), which interacts with both ERI-9 and Dicer and is required for the RdRP-dependent biogenesis of 26G-RNAs (Duchaine et al, 2006; Pavelec et al, 2009; Thivierge et al, 2012). …”
Section: Resultssupporting
confidence: 82%
“…ERI-9 was previously shown to be required for 26G-RNA biogenesis (Pavelec et al, 2009). Consistent with the association of RDE-8 with ERI/Dicer complex components (Duchaine et al, 2006), we found that RDE-8 also co-IPs with the SAP-domain exonuclease ERI-1b (Figure S3; Kennedy et al, 2004), which interacts with both ERI-9 and Dicer and is required for the RdRP-dependent biogenesis of 26G-RNAs (Duchaine et al, 2006; Pavelec et al, 2009; Thivierge et al, 2012). …”
Section: Resultssupporting
confidence: 82%
“…A genome-wide RNAi screen identified these RNAi pathway genes to act redundantly with the KSR-1 (kinase suppressor of Ras) scaffolding protein in Rasmediated excretory duct cell specification (Rocheleau et al 2008). Since DRH-3 is a component of the RdRP complex Thivierge et al 2012) required for the biogenesis of all 22G-RNAs, including those present in the complex with CSR-1 , it is most likely that DRH-3-dependent CSR-1-bound endo-siRNAs regulate a number of genes affecting developmental events, such as HSN migration and excretory duct specification.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, worms employ a distinct analogous signal amplification mechanism that leads to generation of secondary downstream siRNAs upon piRNA: target RNA interaction (on which more below). Despite these apparent differences in the nematode pathway, other protein factors found in Drosophila and mice have also been implied in piRNA silencing in C. elegans: tudor-domain proteins have a demonstrated role in endogenous small RNA pathways (Thivierge et al, 2011) and EKL-1 is a TDRD involved in piRNA-dependent siRNA generation (Gu et al, 2009). The C. elegans genome encodes several additional uncharacterised TDRDs and study of their involvement in the piRNA pathway should be an interesting avenue for future research.…”
Section: Piwi Proteins and Pirna Biogenesis In C Elegansmentioning
confidence: 99%